2017
DOI: 10.1158/1078-0432.ccr-16-2586
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis Identifies a Novel AXL–PI3 Kinase–PD-L1 Signaling Axis Associated with Radiation Resistance in Head and Neck Cancer

Abstract: Purpose The primary cause of death due to head and neck squamous cell carcinoma (HNSCC) is local treatment failure. The goal of this study was to examine this phenomenon using an unbiased approach. Experimental design We utilized HPV-negative cell lines rendered radiation resistant (RR) via repeated exposure to radiation, a panel of HPV-negative HNSCC cell lines and three cohorts of HPV-negative HNSCC tumors (n=68, 97, & 114) from patients treated with radiotherapy and subjected to genomic, transcriptomic an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 41 publications
1
79
0
1
Order By: Relevance
“…23 Nevertheless, latest investigation in patient samples further showed increased AXL-PI3K-PD-L1 signaling to radiation resistance in HPV-negative HNC, suggesting the biomarker to be related to treatment failure. 48 In addition, the expression of PD-L1 was also associated to HIF-1alpha and tumor necrosis, implying the aggressive behavior in these tumor cells. 49 Our post hoc analysis supportively showed a trend of lower Neo-BioCT response rate in patients with initial CPS of more than 5% comparing to those equal or less than 5% (28.6% vs 66.7%, respectively, Supporting Information Supplementary Data 2).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…23 Nevertheless, latest investigation in patient samples further showed increased AXL-PI3K-PD-L1 signaling to radiation resistance in HPV-negative HNC, suggesting the biomarker to be related to treatment failure. 48 In addition, the expression of PD-L1 was also associated to HIF-1alpha and tumor necrosis, implying the aggressive behavior in these tumor cells. 49 Our post hoc analysis supportively showed a trend of lower Neo-BioCT response rate in patients with initial CPS of more than 5% comparing to those equal or less than 5% (28.6% vs 66.7%, respectively, Supporting Information Supplementary Data 2).…”
Section: Discussionmentioning
confidence: 95%
“…This remains to be a controversy in HNC, however, because of inconclusive and contradictory clinical evidences to support the theory . Nevertheless, latest investigation in patient samples further showed increased AXL‐PI3K‐PD‐L1 signaling to radiation resistance in HPV‐negative HNC, suggesting the biomarker to be related to treatment failure . In addition, the expression of PD‐L1 was also associated to HIF‐1alpha and tumor necrosis, implying the aggressive behavior in these tumor cells .…”
Section: Discussionmentioning
confidence: 99%
“…The impact of RT on damage in these cases is currently investigated by our group as well as the immunological consequences including the dynamics of the macrophage phenotype following RIT. Just recently, Skinner and colleagues showed that PD‐L1 expression is a biomarker for RT‐treatment failure in HPV‐negative head and neck cancer . Knowledge on the immunological basis for that in concerted view with modulations of the phenotype of tumor‐infiltrating immune cells might further advance therapy concepts in the future.…”
Section: Challenges Of Radioimmunology and Visions For The Future Of Ritmentioning
confidence: 99%
“…Just recently, Skinner and colleagues showed that PD-L1 expression is a biomarker for RT-treatment failure in HPV-negative head and neck cancer. 208 Besides all, one has never to forget that a radiation oncologist is always in the dilemma to assure secure local tumor control by additionally aiming to induce systemic and specific anti-tumor immune responses. Whether it is ethical to change well-established radiation protocols that have been developed over years for best local tumor control has to be discussed for every individual case.…”
Section: Challenges Of Radioimmunology and Visions For The Future Omentioning
confidence: 99%
“…Recently, our group used proteomic and transcriptomic analysis to screen for potential targets associated with poor outcome following radiation in human papillomavirus (HPV)-negative HNSCC clinical samples (4). One novel candidate identified on reverse-phase protein array analysis (RPPA) screening was the BRCA1-associated protein-1 (BAP1), a nuclear deubiquitinating enzyme consisting of 729 amino acids.…”
Section: Introductionmentioning
confidence: 99%